Penentuan Seleksi Atlet Taekwondo Menggunakan Algoritme Support Vector Machine (SVM) - Uswatun Hasanah; Imam Cholissodin; Mochammad Ali Fauzi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Martial arts is an art that in use for defense or defense, protecting one's self when subjected to danger. Taekwondo is a martial art that originated in Korea that uses the hands and feet with the rules and ethics of discipline. Public physical exercise in a prepare taekwondoin i.e. MTH, 300 meter run, run back and forth 6 meters, side kick, back kick, front kick, Crescent kick, block, punch, horses, jump rope, push ups, sit ups, pull ups, backing up, triple hops. The purpose of this research can apply the algorithm support vector machine in determining the selection athlete taekwondo. On this research uses data sets that 116 has 16 parameters. Then the data is divided into training data and test data which used the method with a K-Fold Cross Validation, with k = 10. The result of the implementation of the algorithm of support vector machine for determination of taekwondo athletes in the classification selection qualify and do not qualify for the best accuracy results obtained with the parameters used, namely a comparison ratio data = 90%: 10%, a parameter Î» ( lamda) = 10, the parameter Î³ (gamma) = 0.001, the parameter C (constant) = 1, parameter Ïµ (epsilon) = 0.001 maximum iterations, 30. So the average accuracy is obtained that is 100%.